Development and Study of the Structure and Properties of a Composite Textile Material with Encapsulated Heat-Preserving Components for Heat-Protective Clothing - Irina Cherunova; Nikolai Kornev; Ekaterina Lukyanova; Valery Varavka (Applied Sciences, 2021)
The modern technology of heat-protective clothing is increasingly aimed at maintaining the active function of materials. Adding heat-preserving components into the volume of heat-insulating fibrous materials changes their structure and properties. In this article, the methods of forming the structure of multi-component insulants with heat-preserving components, as well as the study of structural and thermophysical properties, are presented. Composite textile materials were used in this study, namely a 0/30/50/100% Outlast textile (based on polyester fleece, 70%) + Termofiber (fiber-insulated polyester material, 100%). Based on the research, we established the structural parameters of Termofiber fibrous canvas and the Outlast textile. The study of the thermal conductivity of complex combined insulation materials was performed for different temperature conditions (up to +25 °C) and for the proportion of the heat-accumulating textile components. Based on the obtained research results for the development of complex materials from Termofiber + the Outlast textile, the fraction of the Outlast textile component should be limited to no more than 40% for textile shells in clothing that are operated at a temperature of +5 °C or below. Further conditions for determining the composition of the studied materials for clothing can be settled by taking into account the density of the materials, the mass, and the general thermal insulation of clothing.